Strategi Pembinaan Akhlak Santri dan Santriwati di Pondok Pesantren Modern Rahmatul Asri Maroangin Enrekang - Syarwin Dwi Putra; Hasibuddin; Nashiruddin Pilo (Pascasarjana UMI, 2022)
Moral education seeks to create situations and conditions in such a way that students are encouraged and moved in soul and heart to behave and be civilized, or good manners, in accordance with the expectations of educational institutions. In this study, preparations, methods, approaches, and values were used to apply moral development to determine the process and effectiveness of moral development. that the time required to see the success of the coach in implementing moral development depends on the method and approach used. Also look at the readiness of students to accept the methods and approaches applied. The results of this study concluded that the strategy of moral development at the Rahmatul Asri Modern Islamic Boarding School uses several methods and approaches, namely: the hiwar/dialogue method, the qur'ani or prophetic story method, the uswah/exemplary method, the ta'widiyah/habituation method, the tsawab/reward method, methods of fostering cleanliness, and methods of punishment. The approaches are: the personal approach and the attention approach.